Fitness Medicine - Sozen, Hasan (IntechOpen, 2016)
Although fitness and health have similar properties, they are, in reality, two very different concepts. While health refers to the absence of diseases, fitness refers to the degree of body functioning and the ability of the body to handle physical demands. The more efficient the body functions, the higher the level of fitness. The higher the level of fitness, the greater the chance of the body being free of diseases and maintaining a healthy state.